IoT: Electrocardiogram (ECG) Monitoring System - Kristine Joyce P. Ortiz; John Peter O. Davalos; Elora S. Eusebio; Dominic M. Tucay (Institute of Advanced Engineering and Science, 2018)
Internet of Things (IoT) has many applications in the medical field. With remote-information gathering, healthcare professionals can evaluate, diagnose and treat patients in remote locations using telecommunications technology. This study aimed to develop a small-scale electrocardiogram (ECG) monitoring device that will measure heart rates and waveforms and send the data in a database and a web server. An ECG acquisition device was developed using a single-lead heart rate monitor sensor and an Arduino microcontroller. A program, which will process, analyze and upload the ECG data is coded using MATLAB and C# programs. The collected information is viewed in a Graphical User Interface (GUI) display, coded using C# and in a webpage. Rapid Application Technology (RAD) was used in the methodology, which began with a quick design of the system. The hardware and software systems underwent a prototyping cycle for development. Once finished, the integration of the system is conducted to construct a complete IoT-based ECG monitoring system. For testing using t-test, a sample size of 18 and a a= 0.05 is used. Testing resulted into t-test values that lie in the non-critical zone for all ECG parameters, denoting that there is no significant difference between the gathered data. The device’s percent reliability in detecting ECG conditions such as normal sinus rhythm, sinus tachycardia, sinus bradycardia and flatline, is 83.33%. The percent difference for the heart rate is 0.35 %, which falls within the acceptable medical standard of 99% accuracy. The device was deemed functional and reliable.